2014
DOI: 10.1016/j.jaci.2013.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study and admixture mapping identify different asthma-associated loci in Latinos: The Genes-environments & Admixture in Latino Americans study

Abstract: Background Asthma is a complex disease with both genetic and environmental causes. Genome-wide association studies of asthma have mostly involved European populations and replication of positive associations has been inconsistent. Objective To identify asthma-associated genes in a large Latino population with genome-wide association analysis and admixture mapping. Methods Latino children with asthma (n = 1,893) and healthy controls (n = 1,881) were recruited from five sites in the United States: Puerto Ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 60 publications
(71 reference statements)
6
97
0
2
Order By: Relevance
“…Extensive socioeconomic data were collected for each individual as a part of the Genes-Environments & Admixture in Latino Americans II (GALAII) study (17,18) (Materials and Methods and SI Appendix, Table S1). All of the offspring were genotyped, and the genomic ancestries of the offspring and each of their parents were computationally inferred.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive socioeconomic data were collected for each individual as a part of the Genes-Environments & Admixture in Latino Americans II (GALAII) study (17,18) (Materials and Methods and SI Appendix, Table S1). All of the offspring were genotyped, and the genomic ancestries of the offspring and each of their parents were computationally inferred.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, our mathematical model illustrates how recessive risk alleles have inflated homozygosity in populations with strong assortative mating. An important agenda in epidemiology has been to understand the inflated prevalence of asthma and lung diseases such as Hermansky-Pudlak syndrome in Puerto Ricans (17,32). Our analysis suggests that assortative mating can be a significant factor, and it should be incorporated into epidemiological models of these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have shown that genetic African ancestry is associated with increased risk of asthma in Latino children, whereas, conversely, Native American ancestry was associated with lower odds of asthma, and that African ancestry was associated with reduced lung function among children with asthma (23). Furthermore, alleles protective for the risk of asthma have been found to be more common in Native American populations, and, among Latinos, have been found in greater frequency among Mexican populations compared with other Latinos (23)(24)(25). Specific gene variants have also been linked to increased susceptibility of asthma in the presence of air pollution (26)(27)(28).…”
mentioning
confidence: 78%
“…We evaluated genetic ancestry using methods described elsewhere (24). Briefly, we calculated the proportion of genetic ancestry by first genotyping all subjects with the Axiom LAT1 array (World Array 4; Affymetrix, Santa Clara, CA) (30).…”
Section: Outcome Assessment and Covariatesmentioning
confidence: 99%